The representation of the ghetto in Alex La Guma's work - (:unkn) unknown (My University, 1999)
aIn this study, I aimed at dealing with the spatial aspect in Alex la Guma's work, convinced as I was that it was ignored by most of his critics. I have endeavoured to show that it is an important aspect to understand the work of a writer who has written much on the situation of the oppressed classes in South Africa. I have deeply studied themes linked to the ghetto's life such as : violence, death, prison, delinquency and identity crisis. At the same time, I have analysed his narrative structures. In this respect, I have concluded that the representation of South African ghettos in La Guma's work articulates on an antagonistic discourse. What is really described is the medium of the ideological and axiological struggle between the right and the wrong. The fact that most of La Guma's protagonists live in ghettos built by the government means that they are poised against the system. It is the interaction of the system and individuals who can longer bear being victimised, that contitutes the basis of his work. But it is the battle of the individual to maintain his elementary rights, which forms the underlying themes and differentiates his work from those of his contemporary non-white novelists.
Keywords: African Research